2011
DOI: 10.1088/0953-8984/23/49/495402
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation state of europium in halide glasses

Abstract: The luminescent properties of divalent europium ions can be exploited to produce storage phosphors for x-ray imaging applications. The relatively high cost and limited availability of divalent europium halides makes it desirable to synthesize them from the readily available trivalent salts. In this work, samples of pure EuCl3 and fluoride glass melts doped with EuCl3 were processed at 700-800 °C in an inert atmosphere furnace. The Eu oxidation state in the resulting materials was determined using fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Weber et al [91] showed that EuCl3 heated at 710 C for 10 min resulted in almost equal amounts of EuCl2 and EuCl3. This could be important for production of EuCl2 storage phosphors since EuCl2 is more expensive than EuCl3.…”
Section: Materials Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Weber et al [91] showed that EuCl3 heated at 710 C for 10 min resulted in almost equal amounts of EuCl2 and EuCl3. This could be important for production of EuCl2 storage phosphors since EuCl2 is more expensive than EuCl3.…”
Section: Materials Overviewmentioning
confidence: 99%
“…Mössbauer spectra of ZBLAN samples made with ( a ) 5.0 mol % EuCl2; and ( b ) 2.5 mol % EuCl2 and 2.5 mol % EuCl3 [91]. The solid lines represent a fit of the Mössbauer spectra using simple Lorentzian functions.…”
Section: Figurementioning
confidence: 99%
“…Neither oxide nor oxyfluoride medical imaging plates have been developed, so far, but could possibly be in the future. Fluoride glass ceramics have shown great potential as x-ray image plates [613]. The development of new glass-ceramic materials is currently a busy field, especially in the sol-gel area due to the room temperature options for synthesis and ability to produce uniform dispersion of nanoparticles.…”
Section: Glass Ceramicsmentioning
confidence: 99%
“…At this moment, several routes are being explored to reduce costs of Eu 2+ -doped glasses and to achieve a higher total luminescence output [9, 10]. It was shown that during glass melting cheaper Eu 3+ is partially reduced to the more expensive Eu 2+ , meaning that multivalent doping of Eu 2+ and Eu 3+ in the starting materials can reduce costs.…”
Section: Introductionmentioning
confidence: 99%